2021
DOI: 10.1016/j.seppur.2020.117384
|View full text |Cite
|
Sign up to set email alerts
|

Protein purification with nanoparticle-enhanced crystallisation

Abstract: In this study, silica nanoparticle was synthesised and used to promote lysozyme crystallisation effectively against high concentrations of protein impurity (bovine serum albumin (BSA); concentration = 25.0 -50.0 mg/mL vs 5.0 -25.0 mg/mL for lysozyme) at 1 mL scale, demonstrating that crystallisation is a viable and scalable protein purification technology with the aid of heterogeneous nucleants. The silica nanoparticle expedited the crystallisation of lysozyme through the enhancement of nucleation, significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 66 publications
1
15
0
Order By: Relevance
“…Several efforts have been made to improve protein crystallisations and one of the most successful methods is to use engineered interfaces as heteronucleants [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Several efforts have been made to improve protein crystallisations and one of the most successful methods is to use engineered interfaces as heteronucleants [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…34 Figure 2 also shows the size, shape, and porosity of silica that agree with our previous study. 32 Macroporous silica purchased from the commercial supplier had a porous structure, as shown in the SEM image (Figure 2), and had pores with a diameter of 50 nm according to the supplier. 3.2.…”
Section: Resultsmentioning
confidence: 99%
“…29−31 In this work, we focus on the influence of introducing functionalized porous silica templates with differing surface-modified groups on the polymorphic nucleation of CBZ. 32 A mixture of TEOS/ethanol/deionized water (60/960/138 mL) was stirred at 40 °C, and 0.1 M NaOH (42 mL) was added into this mixture. The final mixture was stirred at 40 °C overnight and centrifuged at 6000 rpm for 10 min to recover the silica nanoparticles, which were dried at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study has demonstrated non-porous silica can mitigate the negative impact from protein impurity via adsorption of protein on particle surfaces while no effect of silica particles on protein solubility was observed. 34 Researchers also showed that porous silica have positive impact as heterogenous nucleants. 32,33,35 As shown in Table 1, mesoporous silica had the highest surface area while non-porous silica had the lowest.…”
Section: Effect Of Silica Particles In Pure Lysozyme Batch Crystallisationmentioning
confidence: 99%
“…However, some limited cases of selective crystallisation were also described. 26,[32][33][34][35] Nonetheless, systematic knowledge of crystallisation behaviour of target protein from the mixture is still absent. The reported selective crystallisation cases only focused on specific scenarios either with ultralow protein concentration, with a very limited range of protein composition of the mixture, or at relatively small scale and long-time span which are not suitable for industrial application.…”
Section: Introductionmentioning
confidence: 99%